A method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column
Through the three-dimensional bi-continuous emulsion template method and coagulation bath regeneration technology, a three-dimensional bi-continuous high-penetration cellulose monolithic column with high mechanical strength and high penetration pores was prepared, which solved the problem of existing polysaccharide monolithic columns in terms of mechanical strength and pore penetration. It achieves high efficiency and biocompatibility in the separation of biological macromolecules.
Patent Information
- Application Number
- CN202410279288.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-12
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-03-12
AI Technical Summary
During the preparation process, existing polysaccharide columns have problems such as low mechanical strength, poor pore penetration, and easy shrinkage after lyophilization, making it difficult to take into account biocompatibility, separation capacity and separation efficiency.
The three-dimensional bi-continuous emulsion template method is used to form a three-dimensional bi-continuous MIPE through the hydrogen bonding and hydrophobic force of the oil-water two-phase surfactant and the cellulose molecular chain at the interface. It is pre-crosslinked and regenerated using a coagulation bath for further chemical cross-linking. A three-dimensional bicontinuous high-penetration cellulose monolithic column with ideal mechanical strength was prepared.
It achieves controllable size of the cellulose monolithic column, three-dimensional continuity of the skeleton and pores, improves mechanical strength and permeability, and is suitable for immobilizing enzymes or separating and purifying biological macromolecules.
Smart Images

Figure CN117959769B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a monolithic column material, and in particular to a method for preparing a three-dimensional double-continuous high-penetration cellulose monolithic column. Background Art
[0002] Biomacromolecules (such as proteins, plasmids, viral vaccines, etc.) are one of the hot areas of life science research. Due to their complexity, diversity and easy inactivation, their large-scale separation and purification has always been a challenge. The separation cost usually accounts for 60-90% of the total product cost. The key to solving this problem is to find an efficient biological separation medium. The monolithic column that appeared in the early 1990s is also known as the fourth generation of chromatographic separation medium (Anal. Chem., 2006, 78, 2101-2107). It has the characteristics of fast operating flow rate, high permeability, low back pressure, and low solute mass transfer resistance. It can effectively avoid the depolymerization of multi-subunit biomacromolecules and has a high activity recovery rate. It is especially suitable for the rapid separation and analysis of biomacromolecules. According to different matrix materials, monolithic columns can be divided into four categories, namely organic polymers, inorganic silica gels, organic-inorganic hybrids, and polysaccharide monolithic columns. Inorganic silica monoliths have low pH tolerance, complex preparation process and poor reproducibility, and are usually used to separate small molecules; organic polymer monoliths are difficult to reconcile in the process of separating biomacromolecules, and are easy to swell in organic solvents, with uneven skeletons and lack of mesoporous structure; similar to polymer monoliths, hybrid monoliths have the same inherent defects. Polysaccharide (agarose, cellulose, starch, etc.) monoliths have good biocompatibility, are rich in hydroxyl groups and are easy to derivatize. Polysaccharide monoliths with ultra-large through-pores have advantages in separating large-sized nucleic acids, plasmids and virus-like particles, which is conducive to maintaining their active structure. Cellulose, as the most abundant natural polymer in nature, has high hydrophilicity, strong solvent resistance, and good mechanical strength. It is an ideal solid support material in the biological field and can replace some petrochemical products to save limited petroleum resources.
[0003] At present, the preparation of polysaccharide monoliths mainly includes thermal induced phase separation, ice condensation induced self-assembly, and emulsion template method. The thermal induced phase separation method requires chemical modification of polysaccharides and selection of suitable organic solvents for dissolution, but the permeability of the formed pores is not ideal, resulting in large mass transfer resistance in the pores of biomacromolecules. The ice condensation induced method can prepare polysaccharide monoliths with three-dimensional skeletons and pore structures, but its biggest problem is that the monoliths after freeze-drying are prone to shrinkage, and the freezing rate control requires precision instruments, which is time-consuming and labor-intensive. The emulsion template method is a powerful tool for preparing porous materials. The pore structure of the material can be easily adjusted by changing the emulsion structure. Common emulsion templates are mainly water-in-oil (O / W) or oil-in-water (W / O) emulsions, which can easily produce closed pores using such templates. Existing literature has used a high internal phase emulsion (HIPE) template method to prepare a monolithic column with a bicontinuous submicron skeleton, but because the volume content of the internal phase reaches 80-90%, the skeleton is very thin and has low mechanical strength, making it difficult to apply (J. Mater. Chem., 2009, 19, 767-772). Compared with HIPE, the internal phase volume of the medium internal phase emulsion (MIPE) is 30-70%. The monolithic column skeleton prepared using MIPE as a template has a high thickness to ensure mechanical strength, but because the internal phase droplets are not connected to each other, most of the formed pores are dead holes, resulting in a low permeability coefficient of the monolithic column that cannot be used. Bicontinuous emulsion refers to the intermediate transition phase that appears during the mutual transformation of O / W type and W / O type emulsions, that is, there are two continuous states in the same system. Due to the coexistence of positive and negative interface curvatures, the bicontinuous system exhibits efficient mass transfer in the oil phase and the water phase, provides a large interface area and allows cross-interface chemical exchange (Small, 2023, 19 (39): 2370315). Different from the traditional structure, in this structure, the water and oil phases are topologically continuous in three-dimensional space, intertwined and distributed, and the two phases are interlocked to form a network structure, which is an ideal template for preparing three-dimensional bicontinuous ultra-large pore monolithic columns.
[0004] Due to its inherent characteristics, the dissolution and regeneration of cellulose is not as easy as that of general polysaccharides, so it is a challenge to prepare cellulose monolithic columns using the emulsion template method. The coagulation bath plays an important role in cellulose regeneration. It is a poor solvent (non-solvent) for cellulose. Commonly used coagulation baths include acids, salts and organic solvents. The role of the coagulation bath is to replace the solvent in the cellulose solution to make it lose its solubility, and the fluid gel gradually transforms into a semi-solid state for precipitation regeneration (Ind Eng Chem Res, 2005, 44 (3): 522-529). Since the coagulation bath replaces the cellulose solvent and is subject to diffusion restriction and large resistance, the cellulose materials prepared by the coagulation bath method in the literature are mainly thin films and micron filaments, and there is no report on the use of the coagulation bath method to prepare cellulose monolithic columns. Summary of the invention
[0005] In view of the problems existing in current research, the purpose of the present invention is to develop a method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column with mechanical strength, biocompatibility, separation capacity and separation efficiency. Through the hydrogen bonds and hydrophobic forces of the oil-water two-phase surfactant and the cellulose molecular chain at the interface, the two phases are interlocked to form a three-dimensional bicontinuous MIPE, which is used as a template for pre-crosslinking and regenerated in a coagulation bath to obtain a size-controllable three-dimensional continuous skeleton and pores, and further chemically crosslinked to obtain a three-dimensional bicontinuous high-throughput cellulose monolithic column with ideal mechanical strength. The monolithic column can be used to immobilize enzymes or separate and purify biomacromolecules. The main challenges of this method are the preparation of a three-dimensional bicontinuous emulsion template, the size control of the bicontinuous region, and the solidification and regeneration process.
[0006] The technical solution adopted by the present invention is:
[0007] A method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column comprises the following steps:
[0008] (1) Using an alkali / urea (thiourea) / water system, cellulose powder is stirred and dissolved at low temperature, and a certain amount of chemical crosslinking agent and water-soluble surfactant are added and stirred evenly to form the water phase. The oil-soluble surfactant and organic solvent are evenly mixed to form the oil phase, and the oil phase is dispersed into the water phase by mechanical stirring, and a stable three-dimensional bicontinuous MIPE is formed after emulsification.
[0009] (2) The emulsion obtained in step (1) is quickly transferred into a plexiglass chromatographic column with a rubber stopper at one end through a syringe, immersed in a coagulation bath to solidify for a period of time, and then the plexiglass chromatographic column is connected to a peristaltic pump, and residual porogens and surfactants are removed using 50% ethanol solution and deionized water in turn.
[0010] (3) using a cross-linking agent to perform secondary cross-linking at a certain temperature and alkaline conditions, and after the cross-linking reaction is completed, washing the monolithic column with a 50% ethanol solution and deionized water to obtain a three-dimensional bicontinuous high-penetration cellulose monolithic column.
[0011] The cellulose powder in step (1) can be microcrystalline fiber or related derivatives, bacterial fiber, bamboo / hemp fiber, and the concentration of the cellulose solution is 1-20wt%.
[0012] The temperature range of dissolving cellulose in step (1) is -5°C to -20°C; the alkali is selected from one of LiOH and NaOH, and the concentration is 4-10wt%; the concentration of urea (thiourea) is 4-20wt%.
[0013] The organic solvent described in step (1) is at least one selected from cyclohexane, n-hexane, n-heptane, ethyl acetate, butyl acetate, dichloroethane, chloroform, carbon tetrachloride, toluene, xylene, chlorobenzene, bromobenzene, liquid paraffin, olive oil, and isooctyl alcohol.
[0014] The water-soluble surfactant described in step (1) is selected from at least one of Tween (such as Tween 20, Tween 40, Tween 60, Tween 80, Tween 85), fatty alcohol polyoxyethylene ether (such as AEO-7, AEO-9, AEO-15, AEO-20, AEO-23, Peregal O-10, Peregal O-15, Peregal O-20, Peregal O-25), alkylphenol polyoxyethylene ether (such as OP-9, OP-10, OP-15, OP-20, OP-30), and polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer (such as F68, F88, F127, F108).
[0015] The oil-soluble surfactant described in step (1) is selected from at least one of Span (such as Span 40, Span 60, Span 65, Span 80), fatty alcohol polyoxyethylene ether (such as AEO-3, AEO-4, AEO-5, AEO-6), alkylphenol polyoxyethylene ether (such as OP-4, OP-5, OP-6, OP-7), and polyoxypropylene-polyoxyethylene-polyoxypropylene copolymer (such as RPE1720, 1740, 2520).
[0016] The mass fraction of the surfactant described in step (1) accounts for 1-15% of the emulsion system, the mixed HLB value ranges from 3.5 to 15, and the HLB value of the mixed emulsifier is calculated according to the mass fraction method.
[0017] The pre-crosslinking step in step (1) is a key step of the present invention, which can ensure the mechanical strength of the cellulose monolithic column after solidification and regeneration. Otherwise, when the peristaltic pump is connected to clean the monolithic column in step (2), the column will be collapsed and cannot be operated; the chemical crosslinking agent can be selected from epichlorohydrin, epichlorohydrin-polyol derivatives, 1,4-butanediol diglycidyl ether, dibutylene oxide, ethylene glycol diglycidyl ether, monoepoxy or polyepoxy compounds and a mixture of one or at least two of multifunctional compounds such as active halogen compounds, and the amount of crosslinking agent added is 1-10% of the volume of the aqueous phase.
[0018] The volume ratio of the water phase to the oil phase in step (1) is 13:7-3:7; the emulsification temperature is 0-30°C; the emulsification time is 3-30min; and the emulsification stirring speed is 200-2000rpm.
[0019] The coagulation bath described in step (2) is selected from one or more of sulfuric acid, hydrochloric acid, acetic acid, boric acid, phytic acid, sulfuric acid / sodium sulfate, ammonium sulfate, ethanol, methanol, acetone or ethylene glycol aqueous solution, and the solution concentration is 1-50wt%; the curing time is 48-96h.
[0020] The base described in step (3) is selected from one of sodium hydroxide, ammonia water, lithium hydroxide, potassium hydroxide, calcium hydroxide, and ammonium hydroxide solution, or a combination of not limited to two.
[0021] The chemical crosslinking agent described in step (3) is the same as that in step (1), with a crosslinking agent mass concentration of 15-50%; a crosslinking temperature of 10-80° C.; a crosslinking reaction time of 6-48 hours, and an alkali concentration range of 0.1-10M.
[0022] The present invention also discloses a three-dimensional bicontinuous high-throughput cellulose monolithic column prepared by the above method, wherein the monolithic column has a three-dimensional bicontinuous skeleton and pore structure, a monolithic column porosity of 55-80%, a through-hole diameter of 1-50 μm, and a specific surface area of 10-50 m 2 / g.
[0023] The present invention is beneficial in that:
[0024] Through the three-dimensional bicontinuous MIPE template method, two nonionic surfactants are used to cooperate hydrogen bonds and hydrophobic forces at the oil-water interface to form an elastic and twisted appearance structure. Different from the traditional MIPE structure, in this structure, the water and oil phases are topologically continuous in three-dimensional space, intertwined and distributed, and the two phases are interlocked to form a three-dimensional network structure. Compared with the low internal phase emulsion and high internal phase emulsion templates, the medium internal phase emulsion template method can take into account both the permeability of the pores and the mechanical strength of the skeleton. Combined with the pre-crosslinking strategy and curing regeneration treatment, a three-dimensional bicontinuous high-permeability cellulose monolithic column is finally obtained. The cellulose monolithic column prepared by this method has a simple preparation process and low cost. The ultra-large pores are highly permeable in three-dimensional space, which can improve the mass transfer rate and diffusion effect. It is particularly suitable for separating large-sized biomacromolecules (virus-like particles, nucleic acids, plasmids, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is an inverted fluorescence morphology image of the three-dimensional bicontinuous MIPE prepared in Example 1.
[0026] Figure 2 This is a scanning electron microscope image of the three-dimensional bicontinuous high-penetration cellulose monolithic column in Example 1.
[0027] Figure 3 This is a scanning electron microscope image of the ultra-macroporous cellulose monolith in the comparative example. DETAILED DESCRIPTION
[0028] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0029] The specific implementation method of the present invention is as follows:
[0030] Embodiment 1:
[0031] (1) Weigh 3.01g of microcrystalline cellulose and add it to a 7wt% NaOH / 12wt% urea solution (40mL) precooled at -12°C, and stir for 10 minutes to dissolve. Take 5mL of the cellulose solution, add 0.35mL of epichlorohydrin and 0.3g of Tween 80, and stir evenly as the aqueous phase. Mix 5mL of cyclohexane and 0.15g of RPE1720 evenly as the oil phase, disperse the oil phase into the aqueous phase by mechanical stirring, and emulsify at 25°C at a speed of 2000rpm for 20 minutes. After emulsification, a stable three-dimensional bicontinuous MIPE is formed. The inverted fluorescence morphology of the three-dimensional bicontinuous MIPE is shown in Figure 1 .
[0032] (2) The emulsion obtained in step (1) is quickly transferred into a plexiglass chromatographic column with a rubber stopper at one end through a syringe, and the column is immersed in a 5 wt % sulfuric acid coagulation bath for curing for 72 h. The plexiglass chromatographic column is then connected to a peristaltic pump, and residual porogens and surfactants are removed using 50% ethanol solution and deionized water in turn.
[0033] (3) Take 4 mL of NaOH (10 M) solution and 8 mL of epichlorohydrin and mix them evenly. Use a peristaltic pump to circulate into the monolithic column for secondary cross-linking. The cross-linking temperature is 45 ° C and the cross-linking time is 10 h. After the reaction is completed, the monolithic column is washed with 50% ethanol solution and deionized water to obtain a three-dimensional bicontinuous high-throughput cellulose monolithic column. The scanning electron microscope photo is shown in Figure 2 .
[0034] Embodiment 2:
[0035] (1) Weigh 4.44 g of microcrystalline cellulose and add it to a 6 wt% NaOH / 5 wt% thiourea solution (40 mL) precooled at -5°C, and stir for 10 min to dissolve. Take 6 mL of the cellulose solution, add 0.48 mL of diepoxybutane and 0.25 g of F108, and stir evenly as the water phase. Mix 4 mL of ethyl acetate and 0.11 g of Span 80 evenly as the oil phase, and disperse the oil phase into the water phase by mechanical stirring. Emulsify at 30°C and 1500 rpm for 30 min to form a stable three-dimensional bicontinuous MIPE after emulsification.
[0036] (2) The emulsion obtained in step (1) is quickly transferred into a plexiglass chromatographic column with a rubber stopper at one end through a syringe, and the column is immersed in a 10 wt % sulfuric acid / sodium sulfate coagulation bath for curing for 96 h. The plexiglass chromatographic column is then connected to a peristaltic pump, and residual porogens and surfactants are removed using 50% ethanol solution and deionized water in turn.
[0037] (3) 4 mL of NaOH (10 M) solution and 8 mL of diepoxybutane were uniformly mixed and circulated by a peristaltic pump for secondary crosslinking at a crosslinking temperature of 45° C. for 14 h. After the reaction, the monolithic column was washed with 50% ethanol solution and deionized water to obtain a three-dimensional bicontinuous high-throughput cellulose monolithic column.
[0038] Embodiment 3:
[0039] (1) Weigh 3.01g of bamboo fiber and add 9.3wt% NaOH / 7.4wt% thiourea solution (40mL) precooled at -10℃, stir for 10min to dissolve. Take 6mL of cellulose solution, add 0.51mL 1,4-butanediol diglycidyl ether and 0.19g Tween 80 and stir evenly as the water phase. Mix 4mL of toluene and 0.17g OP-5 evenly as the oil phase, disperse the oil phase into the water phase by mechanical stirring, emulsify at 25℃ and 2000rpm for 20min, and form a stable three-dimensional bicontinuous MIPE after emulsification.
[0040] (2) The emulsion obtained in step (1) is quickly transferred into a plexiglass chromatographic column with a rubber stopper at one end through a syringe, and the column is immersed in a 20 wt % methanol coagulation bath for solidification for 96 h. The plexiglass chromatographic column is then connected to a peristaltic pump, and residual porogens and surfactants are removed using 50% ethanol solution and deionized water in turn.
[0041] (3) 4 mL of KOH (10 M) solution and 8 mL of 1,4-butanediol diglycidyl ether were mixed evenly and circulated by a peristaltic pump for secondary crosslinking at a crosslinking temperature of 45° C. for 10 h. After the reaction, the monolithic column was washed with 50% ethanol solution and deionized water to obtain a three-dimensional bicontinuous high-throughput cellulose monolithic column.
[0042] Embodiment 4:
[0043] (1) Weigh 3.01g of hemp fiber and add 7.5wt% NaOH / 11wt% urea solution (40mL) precooled at -10℃, stir for 10min to dissolve. Add 0.3mL of ethylene glycol diglycidyl ether and 0.29g of perchlorate O-25 to 5mL of cellulose solution and stir evenly as the water phase. Mix 5mL of xylene and 0.14g of RPE1720 evenly as the oil phase, disperse the oil phase into the water phase by mechanical stirring, emulsify at 25℃ and 1800rpm for 25min, and form a stable three-dimensional bicontinuous MIPE after emulsification.
[0044] (2) The obtained emulsion was quickly transferred into a plexiglass chromatographic column with a rubber stopper at one end through a syringe, and the column was immersed in a 5 wt % hydrochloric acid coagulation bath for curing for 72 h. The plexiglass chromatographic column was then connected to a peristaltic pump, and residual porogens and surfactants were removed using 50% ethanol solution and deionized water in turn.
[0045] (3) 4 mL of NaOH solution (10 M) and 8 mL of ethylene glycol diglycidyl ether were mixed evenly and circulated by a peristaltic pump for secondary crosslinking at a crosslinking temperature of 45° C. for 12 h. After the reaction, the monolithic column was washed with 50% ethanol solution and deionized water to obtain a three-dimensional bicontinuous high-throughput cellulose monolithic column.
[0046] Embodiment 5:
[0047] (1) Weigh 4.55g of bacterial cellulose and add 4.6wt% LiOH / 15wt% urea solution (40mL) precooled at -15℃, stir for 10min to dissolve. Take 5mL of cellulose solution, add 0.4mL 1,4-butanediol diglycidyl ether and 0.20g OP-20 and stir evenly as the water phase. Mix 5mL cyclohexane and 0.09g RPE2520 evenly as the oil phase, disperse the oil phase into the water phase by mechanical stirring, emulsify at 20℃ and 2000rpm for 20min, and form a stable three-dimensional bicontinuous MIPE after emulsification.
[0048] (2) The emulsion obtained in step (1) is quickly transferred into a plexiglass chromatographic column with a rubber stopper at one end through a syringe, and the column is immersed in a 40wt% ethanol coagulation bath for curing for 96 hours. The plexiglass chromatographic column is then connected to a peristaltic pump, and residual porogens and surfactants are removed using 50% ethanol solution and deionized water in turn.
[0049] (3) Take 4 mL of LiOH solution (10 M) and 8 mL of 1,4-butanediol diglycidyl ether and mix them evenly. Use a peristaltic pump to circulate and pump them in for secondary crosslinking. The crosslinking temperature is 45° C. and the crosslinking time is 12 h. After the reaction is completed, the monolithic column is washed with 50% ethanol solution and deionized water to obtain a three-dimensional bicontinuous high-throughput cellulose monolithic column.
[0050] Comparative Example:
[0051] (1) Weigh 3.01 g of microcrystalline cellulose and add it to a 7 wt% NaOH / 12 wt% urea solution (40 mL) precooled at -12°C, and stir for 10 min to dissolve. Take 5 mL of the cellulose solution, add 0.35 mL of epichlorohydrin and 0.3 g of Tween 80, and stir evenly to form the aqueous phase. Take 5 mL of cyclohexane as the oil phase, disperse the oil phase into the aqueous phase by mechanical stirring, and emulsify at 25°C at a speed of 2000 rpm for 20 min to obtain an oil-in-water emulsion.
[0052] (2) The emulsion obtained in step (1) is quickly transferred into a plexiglass chromatographic column with a rubber stopper at one end through a syringe, and the column is immersed in a 5 wt % sulfuric acid coagulation bath for curing for 72 h. The plexiglass chromatographic column is then connected to a peristaltic pump, and residual porogens and surfactants are removed using 50% ethanol solution and deionized water in turn.
[0053] (3) Take 4 mL of NaOH (10 M) solution and 8 mL of epichlorohydrin and mix them evenly. Use a peristaltic pump to circulate into the monolithic column for secondary cross-linking. The cross-linking temperature is 45 ° C and the cross-linking time is 10 h. After the reaction is completed, the monolithic column is washed with 50% ethanol solution and deionized water to obtain an ultra-large pore cellulose monolithic column. The scanning electron microscope photo is shown in Figure 3 .
[0054] The pore size, specific surface area and porosity of the monolithic column obtained in the above experiment are shown in Table 1.
[0055] Table 1 Comparison of pore size, porosity and specific surface area of cellulose monolithic column between the embodiment and the comparative example
[0056]
[0057] Effect experiment:
[0058] The scanning electron microscope was used to observe the Figure 2 ) and comparative example ( Figure 3) shows that the former has a three-dimensional bicontinuous high-throughput pore structure, while many pores of the monolithic column obtained by the water-in-oil emulsion are not connected. This is due to the fact that the oil-water two-phase surfactant and the cellulose molecular chain form a three-dimensional bicontinuous MIPE at the interface through hydrogen bonding and hydrophobic interaction, and after further regeneration, a three-dimensional skeleton structure and high-throughput pores can be obtained. The pressure flow rate curve of the monolithic column prepared in Example 1 and the comparative example was measured, and the maximum flow rates were 2980cm / h and 994cm / h, respectively. The permeability coefficients calculated by Darcy's law were 1.9×10 -12 m 2 and 6.3×10 -13 m 2 , indicating that the three-dimensional bicontinuous high-penetration cellulose monolithic column has better permeability performance and higher mechanical strength, and can be used for separation operations at high flow rates.
Claims
1. A method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column, characterized in that the steps include: (1) Using an alkali / urea / water system or an alkali / thiourea / water system, cellulose powder is stirred and dissolved at low temperature, a certain amount of chemical crosslinking agent and water-soluble surfactant are added, and the mixture is stirred evenly to form the water phase; an oil-soluble surfactant and an organic solvent are evenly mixed to form the oil phase, and the oil phase is dispersed into the water phase by mechanical stirring, and a stable three-dimensional bicontinuous inner phase emulsion is formed after emulsification; (2) The emulsion obtained in step (1) is quickly transferred into a plexiglass chromatographic column with a rubber stopper at one end through a syringe, and the plexiglass chromatographic column is immersed in a coagulation bath for a period of time for solidification, and then the plexiglass chromatographic column is connected to a peristaltic pump, and residual porogens and surfactants are removed using 50% ethanol solution and deionized water in turn; (3) using a cross-linking agent to perform secondary cross-linking at a certain temperature and alkaline conditions, and after the cross-linking reaction is completed, washing the monolithic column with a 50% ethanol solution and deionized water to obtain a three-dimensional bicontinuous high-penetration cellulose monolithic column; The water-soluble surfactant described in step (1) is selected from at least one of Tween, water-soluble fatty alcohol polyoxyethylene ether, water-soluble alkylphenol polyoxyethylene ether, and polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer; the oil-soluble surfactant is selected from at least one of Span, oil-soluble fatty alcohol polyoxyethylene ether, oil-soluble alkylphenol polyoxyethylene ether, and polyoxypropylene-polyoxyethylene-polyoxypropylene copolymer.
2. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The cellulose powder in step (1) can be microcrystalline fiber or related derivatives, bacterial fiber, bamboo / hemp fiber, and the concentration of the cellulose solution is 1-20 wt%.
3. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The organic solvent described in step (1) is at least one selected from cyclohexane, n-hexane, n-heptane, ethyl acetate, butyl acetate, dichloroethane, chloroform, carbon tetrachloride, toluene, xylene, chlorobenzene, bromobenzene, liquid paraffin, olive oil, and isooctyl alcohol.
4. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The Tween is selected from Tween 20, Tween 40, Tween 60, Tween 80, and Tween 85, the water-soluble fatty alcohol polyoxyethylene ether is selected from AEO-7, AEO-9, AEO-15, AEO-20, AEO-23, Peregal O-10, Peregal O-15, Peregal O-20, and Peregal O-25, the water-soluble alkylphenol polyoxyethylene ether is selected from OP-9, OP-10, OP-15, OP-20, and OP-30, and the polyoxyethylene-polyoxypropylene-polyoxyethylene copolymer is selected from F68, F88, F127, and F108.
5. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The Siban is selected from Siban 40, Siban 60, Siban 65 and Siban 80, the oil-soluble fatty alcohol polyoxyethylene ether is selected from AEO-3, AEO-4, AEO-5 and AEO-6, the oil-soluble alkylphenol polyoxyethylene ether is selected from OP-4, OP-5, OP-6 and OP-7, and the polyoxypropylene-polyoxyethylene-polyoxypropylene copolymer is selected from RPE1720, 1740 and 2520.
6. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The sum of the mass fractions of the water-soluble surfactant and the oil-soluble surfactant described in step (1) accounts for 1-15% of the emulsion system, the mixed HLB range is 3.5-15, and the HLB value of the mixed emulsifier is calculated according to the mass fraction method.
7. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The chemical crosslinking agent described in step (1) is selected from one or a mixture of at least two of epichlorohydrin, epichlorohydrin-polyol derivatives, 1,4-butanediol diglycidyl ether, dibutylene oxide, ethylene glycol diglycidyl ether, monoepoxy or polyepoxy compounds, and polyfunctional compounds containing active halogen compounds, and the amount of the crosslinking agent added is 1-10% of the volume of the aqueous phase.
8. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The volume ratio of the water phase to the oil phase in step (1) is 13:7-3:7; the emulsification temperature is 0-30°C; the emulsification time is 3-30 min; and the emulsification stirring speed is 200-2000 rpm.
9. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The coagulation bath in step (2) is selected from one or more of sulfuric acid, hydrochloric acid, acetic acid, boric acid, phytic acid, sulfuric acid / sodium sulfate, ammonium sulfate, ethanol, methanol, acetone or ethylene glycol aqueous solution, and the solution concentration is 1-50 wt%; the curing time is 48-96 h.
10. The method for preparing a three-dimensional bicontinuous high-throughput cellulose monolithic column according to claim 1, characterized in that: The chemical crosslinking agent in step (3) is the same as that in step (1), with a crosslinking agent mass concentration of 15-50%; a crosslinking temperature of 10-80°C; a crosslinking time of 6-48 h; and an alkali concentration range of 0.1-10 M.
Citation Information
Patent Citations
Macroporous agarose microspheres and preparation method thereof
CN103055773A
Novel high-strength uniform-strength cellulose microsphere preparation method
CN108745219A
High-strength polysaccharide-inorganic nanoparticle composite monolithic column and preparation method thereof
CN116116390A